KARAKTERISTIK PENDERITA HEMOROID DARI HASIL PEMERIKSAAAN KOLONOSKOPI DI RSUD DR. PIRNGADI MEDAN - Butar - Butar, Syarifuddin Hizkia; Tarigan, Pengarapen; Lumongga, Fitriana (Universitas Methodist Indonesia, 2020)
Background : Hemoroid is enlargement of superior hemorrhoidal plexus vein.hemorrhoid will become more serverif no action is taken immediately. Usia> 45 years had higher risk of developing hemorrhoids. Man has the risk factor affected by hemorrhoids and this incident also experienced by women who are pregnant and someone who is obes. Eventually, there will be bulging hemorrhoids that can not be put back into the anus, so the operation should be carried out. Method :This study was an description research with cross sectional method and and from colonoscopy result and using secondary data obtained from medical record of Pirngadi Medan Hospital period of 2013-2015. Sample selection is done using consecutive sampling method and was obtained from medical record. Result : male subjects who suffered hemorrhoids more record from age is 36-45 years are 33 subjects ( 52,3%), and from gender, male subjects who suffered hemorrhoids are 55 subjects (63,5%), and profession who suffered hemorroids are farmers 29 subjects (36,5%), and finally,education subject who suffered hemorrhoids are SLTA 33 subjects (35,6%). There wa relation between age with the degree of hemorrhoids. Conclution ; Total sample obtained as many as 79 people suffering from hemorroids. The higher a person’s age the hemorroid that he sustained will get worse.